Embedded indexing with Word. Part 4 – page reference annotations and functional ebook indexes. (1st March 2021) - Greulich, Walter
Abstract : In this fourth article in a series on the under-exploited potential for using Microsoft Word as a tool for embedded indexing, the focus is on creating page-reference annotations and the automatic linking of index entries when producing an ebook from the Word document. Also described is the transfer from Word to ebook by using the ebook programs Jutoh and Sigil. The first three articles in the series can be found in the June, September and December 2020 issues of The Indexer (38(2), 38(3) and 38(4)).